O uno e os éons: A soteriologia em plotino e em sua polêmica antignóstica - Gallego, Roberto de Almeida (2006)
The aim of the present study is to explore the issue of salvation as proposed by Plotinus who was both a philosopher and a mystic, and the most noteworthy representative of the last period of Greek philosophy and also the experience of gnosis, an important religious movement that reached its climax in the first centuries of the Christian Era. Initially, the study sought to contextualize this theme within the historical framework in which the socalled Plotinus s antignostic polemic occurred, namely, during the Late Antiquity, when the notion prevailed that the earthly existence replete with suffering and privation would have to be transcended. The human being was but a stranger in the world that surrounded them and, therefore, should return to their spiritual homeland, their true ancestry. It was within this historical context that Plotinus s and the Gnostics doctrine on salvation took place. Although they converged on some of its aspects, there existed a profound divergence of views between them. This study also sought to outline the fundamental concepts behind confront systems. With regard to the Gnostics, the Sethian school was analyzed since it formulated two Gnostic treatises contained in the so-called Nag Hammadi Library , which were acknowledged and criticized by Plotinus: the Zostrianus and Allogenes. In addition, the study went on to examine the theme of salvation vis a vis the theories of cosmogony/cosmology, anthropogony/anthropology, and ethics of the Plotinian and Gnostic systems, especially the Sethian Gnostic texts. Lastly, the study focused on the salvationary aspects of both traditions, the role ascribed to man in the redemption process, and also the scope of salvation. As the basis for research, works by Brazilian and foreign commentators were resorted to, as well as primary sources such as Plotinus s Enneads and the Gnostic treatises held in the Nag Hammadi Library , mainly the aforementioned Zostrianus and Allogenes. The reason for undertaking this research lies in the fact that in Brazil there are few studies about the relationship between Plotinus and the Gnostics, and there are even fewer studies conducted in the spectrum of their soteriology. Therefore, the present research hopes to arouse the interest of Brazilians for the study of philosophical and religious construction addressing the fundamental issues of the human soul